The Gilles de la Tourette Syndrome-Quality of Life Scale (GTS-QOL): A Validation in Japanese Patients - Goto, Ryunosuke; Matsuda, Natsumi; Nonaka, Maiko; Hamamoto, Yu; Eriguchi, Yosuke; Fujiwara, Mayu; Suzuki, Akane; Yokoyama, Yukari; Kano, Yukiko (Frontiers in Psychiatry, 2022)
Background Though Gilles de la Tourette’s syndrome (GTS) has significant impact on the quality of life of its patients, measures of health-related quality of life (HR-QOL) specific to adolescents and adults with GTS were not developed until recently. The present study provides evidence on the validity of the Gilles de la Tourette Syndrome-Quality of Life Scale (GTS-QOL), the first disease-specific HR-QOL instrument for GTS patients, for the first time in an East Asian sample. Methods 102 Japanese individuals aged 13 and above with GTS were included in our study. Internal consistency was evaluated using Cronbach’s alpha. The 4-factor structure of the GTS-QOL was assessed using confirmatory factor analysis, using goodness of fit indices, factor loadings of each questionnaire item, and covariances between factors. Validity was assessed using interscale correlations. Convergent and discriminate construct validity was evaluated using correlations with other scales such as the 28-item General Health Questionnaire, the Yale Global Tic Severity Scale, and the short version of the Padua Inventory. Results Scaling assumptions were met. Internal consistency reliability was high, with a Cronbach’s alpha of 0.96. Confirmatory factor analysis revealed sufficient factor loadings and goodness of fit. All measures of goodness of fit corroborated the fit of the 4-factor model. Standardized covariances between factors in the confirmatory factor analysis were greater than 0.8. There were significant correlations with other well-validated scales, and thus convergent and discriminate construct validity was sufficient. Conclusion The GTS-QOL is a valid and reliable instrument to measure disease-specific HR-QOL of GTS patients in Japan.